Guideline on the Development of Digital Leadership for Schools Administrator of Secondary Schools under the Office of the Basic Education Commission - Thurongkinanon, Kanokwon; Trakulkasemsuk, Prapawan (Journal of Thammawat, 2024)
This article aims to 1) study the digital leadership of secondary school administrators 2) propose guidelines for developing the digital leadership of secondary school administrators under the Office of the Basic Education Commission. This was a qualitative research study of data from In-depth interviews with five key informants and descriptive data analysis. The results of the research found that the digital leadership of secondary school administrators consists of six important factors: (1) digital vision and strategy, (2) knowledge and ability to lead the use of digital ethically, (3) Digital technology management (4) environment management and digital technology innovation (5) personnel development to have digital knowledge, ability and competency (6) communication to create motivation and participation. And the guidelines for developing the digital leadership of secondary school administrators in all 6 areas had 26 guidelines, namely, Area 1: Digital vision and strategy, there were 5 approaches such as developing digital vision and strategy, Area 2: Know your abilities and be a leader in the use of digital with ethics. There were 4 approaches, such as developing knowledge and skills in using digital technology in both software and hardware. Area 3: Digital technology management had 5 approaches, such as developing systems. Manage school infrastructure, aspect 4: organizing the environment and innovation in digital technology, had 4 approaches, such as creating an academic ecosystem to have an atmosphere like a digital educational institution, aspect 5: developing personnel to have knowledge, abilities and competencies. There were 4 approaches to digital such as developing personnel to have digital knowledge, abilities and competencies and Area 6: Communication to create motivation and participation had 4 approaches, such as developing communication.